Complex I deficiency in m.3243A>G fibroblasts is alleviated by reducing NADH accumulation - Liufu, Tongling; Yu, Haiyan; Yu, Jiaxi; Yu, Meng; Tian, Yue; Ou, Yichun; Deng, Jianwen; Xing, Guogang; Wang, Zhaoxia (Frontiers in Physiology, 2023)
Mitochondrial disease is a spectrum of debilitating disorders caused by mutations in the mitochondrial DNA (mtDNA) or nuclear DNA that compromises the respiratory chain.Mitochondrial 3243A>G (m.3243 A>G) is the most common mutation showing great heterogeneity in phenotype. Previous studies have indicated that NADH: ubiquinone oxidoreductase (complex I) deficiency accompanied by a decreased nicotinamide adenine dinucleotide (NAD + )/reduced NAD + (NADH) ratio may play a pivotal role in the pathogenesis of m.3243A>G mutation. To evaluate the potential effects of strategies targeting the imbalanced NAD + /NADH ratio in m.3243A>G mutation, we treated fibroblasts derived from patients with the m.3243 A>G mutation using nicotinamide riboside (NR) or mitochondria-targeted H2O-forming NADH oxidase (mitoLbNOX). M.3243 A>G fibroblasts showed a significant reduction in complex I core subunit 6, complex I enzymatic activity, complex I-dependent oxygen consumption rate (OCR), and adenosine triphosphate (ATP) production compared to the controls.The NAD + /NADH ratio was also significantly reduced in m.3243 A>G fibroblasts, and, using fluorescence lifetime imaging microscopy, we also found that the NADH level was elevated in m.3243 A>G fibroblasts. After NR treatment, the NAD + /NADH ratio, complex I-dependent OCR, and ATP levels increased, whereas NADH levels remained unchanged. More excitingly, after treatment with mitoLbNOX, the NAD + /NADH ratio, complex I-independent OCR, and ATP levels increased more pronouncedly compared with the NR treatment group, accompanied by Complex I deficiency in m.3243A>G significantly reduced NADH levels. The present study suggests that compared with repletion of NAD + alone, the combination of this therapeutic modality with alleviation of NADH overload may amplify the treatment effect of restoring NAD + /NADH balance in m.3243A>G fibroblasts.